Characteristics of Consumers Who are Loyal in Buying Food Product at Cafe Pelangi Ambon City - Alhabsyi, Putri Nabila; Turukay, Martha; Simanjorang, Tienni Mariana (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the characteristics of consumers who are loyal in buying food products at Cafe Pelangi in Ambon City. The research method used in this research is descriptive analytic. The sampling technique used was purposive sampling technique so that 70 respondents were obtained. The results showed that the majority of loyal consumers at Cafe Pelangi are men aged 30-49 years with high school and bachelor education levels, predominantly self-employed with middle to upper income. In addition, high frequency of visits, satisfaction with food products, and a comfortable atmosphere are the main factors that influence consumer loyalty. The results of this study provide important implications for Cafe Pelangi in designing more targeted marketing strategies, such as developing new menus that suit the preferences of loyal consumers and improving service quality